Influence of the hardening characteristics of material on the critical load in the elasto-plastic stability problem of conical shells - Bich, Dao Huy; Bay, Vu Khac (Vietnam Journal of Mechanics, 2006)
In this paper by using the theory of elasto-plastic processes and adjacent equilibrium criterion the governing equations of the elasto-plastic stability problem of conical shells are derived. The Bubnov-Galerkin’s method combined with the loading parameter method are applied in solving the mentioned problem. The influence of the hardening characteristics of material on the critical load is investigated